Assistance in Designing Liquid Organic Fertilizer Labels Produced by Poktan Cemerlang - Erni Hawayanti; Innike Abdillah Fahmi; Mustopa Marli Batubara; Rafeah Abubakar; Harniatun Iswarini; Rahmat Kurniawan; Muhamad Sidik (Altifani Journal: International Journal of Community Engagement, 2023)
Labels are an important factor in marketing a product, especially organic fertilizer products which have the provisions stipulated in the Minister of Agriculture No. 01 of 2019. This activity aims to provide knowledge about labels on organic fertilizer products and provide assistance in designing organic fertilizer labels. The method of implementing this service is in the form of socializing labels on organic fertilizers and assistance in designing organic fertilizer labels produced by Poktan Cemerlang as partners in this activity. The participants involved were 20 people who were members of the Cemerlang Poktan. The evaluation carried out in this activity was in the form of giving pre-test and post-test questionnaires related to understanding the labeling material on organic fertilizers. The results of this activity showed that there was an increase in participants' understanding of the labeling material for organic fertilizer products, from 24% (pre-test) to 77.5% (post-test). And Poktan Cemerlang has been able to design labels for liquid organic fertilizer products to be produced. However, for legality and distribution licenses that have not been completed on the label, it is hoped that there will be assistance for legality registration and distribution permits for organic fertilizer products so that they can be marketed.